2021
DOI: 10.1007/s10896-021-00292-3
|View full text |Cite
|
Sign up to set email alerts
|

‘I Think it Just Made Everything Very Much More Intense’: A Qualitative Secondary Analysis Exploring The Role Of Friends and Family Providing Support to Survivors of Domestic Abuse During The COVID-19 Pandemic

Abstract: The COVID-19 pandemic, and associated social restrictions, have amplified women’s experiences of domestic abuse (DA). In usual times, female DA survivors reach out to those around them (friends, family members, neighbors, and colleagues) for support. Accessing of both professional and informal support by survivors has increased during the pandemic. Informal supporters are often deeply invested and immersed in situations of DA because of the closeness of relationships. The accounts of informal supporters are ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…While there was little indication that the severity of abuse itself increased, there was certainly agreement that the frequency of abuse was amplified during lockdown. Our findings align with and emphasise recent reports of 'pandemic-specific abuse' (Davidge, 2020;Gregory & Williamson, 2021), where perpetrators were seen to capitalise on the pandemic context in COVID-19 LOCKDOWN AND DOMESTIC ABUSE 22 their abusive tactics. DAH staff consistently provided examples of how abusers were using government restrictions to add weight and justification to their abusive and controlling behaviours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While there was little indication that the severity of abuse itself increased, there was certainly agreement that the frequency of abuse was amplified during lockdown. Our findings align with and emphasise recent reports of 'pandemic-specific abuse' (Davidge, 2020;Gregory & Williamson, 2021), where perpetrators were seen to capitalise on the pandemic context in COVID-19 LOCKDOWN AND DOMESTIC ABUSE 22 their abusive tactics. DAH staff consistently provided examples of how abusers were using government restrictions to add weight and justification to their abusive and controlling behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…Family members of those living with DA have similarly reported that COVID-19 lockdown impeded their ability to assess the level of danger faced given that there were no opportunities to identify cues that the abuse was still ongoing or had worsened (Gregory & Williamson, 2021). Informal support seeking from friends and family often marks an important first step in pursuing help for DA victims, whereby positive informal support seeking experiences increase the likelihood of progressing to engage with formal support services (Goodman et al, 2005;Plazaola-Castano et al, 2008).…”
Section: Covid-19 Lockdown and Domestic Abusementioning
confidence: 99%
“…A few qualitative studies have already helped to address this gap in our understanding of experiences of DV during COVID. Other qualitative studies examining perspectives of survivors and families have been published in India (Huq et al, 2021), Greece (Chatzifotiou & Andreadou, 2021), and England (Gregory & Williamson, 2021). Recent work by van Gelder et al (2021) examined the increasing professional and personal challenges that providers in the Netherlands experienced while supporting survivors remotely during the first wave of the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…31 That children increasingly initiated contact may reflect constraints placed on survivors by the pandemic. 32 These results highlight the importance of prioritizing support of children and young people impacted by domestic abuse in the pandemic recovery who were not reached by specialist services, 23 but were, as our analysis shows, the main source of third party referrals to police during the lockdown months. Specialist services for children experiencing domestic abuse need to be prioritized for funding, together with training for other agencies, such as the police, to help them understand the impact of domestic abuse on children, increase their comfort in talking to children about abuse and importantly how to refer them to specialist support.…”
Section: What This Study Addsmentioning
confidence: 67%
“…Our finding relating to the rise of third parties making police reports as the lockdown period ended also supports the calls made by specialist domestic abuse charities 23 to extend campaigns such as 'Ask for ANI' to other services such as banks, supermarkets and to encourage friends, family and neighbours to 'Reach In' to those who may be experiencing abuse. 32 However, frontline domestic abuse services have expressed concern over partner agency capacity, 23 particularly in relation to the delay in accessing mental health services for both adults and children. Our findings have highlighted the importance of mental health services for Children and Young People being adequately funded to meet this increased demand, in order for specialist domestic abuse services to refer for counselling and other support that can be accessed in a timely way and support families' recovery from abuse.…”
Section: What This Study Addsmentioning
confidence: 99%